Castasterone, a Plant Steroid Hormone, Affects Human Small-Cell Lung Cancer Cells and Reverses Multi-Drug Resistance - David Sadava; Shiuan Chen (MDPI AG, 2023)
Small-cell lung cancer (SCLC) has a dismal prognosis, in part because of the development of multi-drug resistance. Castasterone (CAS) is the metabolic precursor of the plant steroid hormone epibrassinolide (EB). In some plants, EB accounts for the total hormone activity, whereas in other plants, CAS is the active form. The effects of CAS, a BR present in most plants, on animal cells in general and cancer cells in particular have not been described. Here, we report the effects of CAS on drug-sensitive (H69) and drug-resistant (VPA17) SCLC cells. CAS was equally cytotoxic to both cell lines (IC50 = 1 μM), indicating a lack of cross-resistance. Pre-incubation of VPA17 cells with CAS for 96 h reversed drug resistance to etoposide and doxorubicin. Synergism between CAS and EB, as well as with chemotherapy drugs, was investigated by exposure of VPA17 cells to 1:1 ratios of CAS and the other drugs at the respective IC50 values, with dilutions at 0.25 to 2.0 × IC50 and determination of the combination index (CI). CAS and EB were additive, indicating that the two drugs act on the same pathway, whereas CAS-etoposide (CI = 0.77) and CAS-doxorubicin were synergistic, indicating that CAS and the two chemotherapeutic drugs act on different pathways. Apoptosis in SCLC cells was measured by immuno-detection of single-strand DNA breaks. Following 96 h incubation of SCLC H69 cells in CAS, the level of DNA breaks was similar to measurements made after incubation in EB and etoposide, indicating that CAS is pro-apoptotic. Incubation of SCLC cells in CAS led to a time-dependent reduction (by 80%) in the transcriptional activator β-catenin. These data indicate that CAS may act via Wnt signaling. Taken together, our study reveals that CAS is pharmacologically active in both drug-sensitive and drug-resistant SCLC cells.